2005
DOI: 10.1161/circulationaha.104.527226
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-Derived Nitric Oxide Regulates Postischemic Myocardial Oxygenation and Oxygen Consumption by Modulation of Mitochondrial Electron Transport

Abstract: Background-Nitric oxide (NO) production is increased in postischemic myocardium, and NO can control mitochondrial oxygen consumption in vitro. Therefore, we investigated the role of endothelial NO synthase (eNOS)-derived NO on in vivo regulation of oxygen consumption in the postischemic heart. Methods and Results-Mice were subjected to 30 minutes of coronary ligation followed by 60 minutes of reperfusion.Myocardial oxygen tension (PO 2 ) was monitored by electron paramagnetic resonance oximetry. In wild-type, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
137
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 114 publications
(153 citation statements)
references
References 52 publications
16
137
0
Order By: Relevance
“…The procedure for the in vivo ischemia-reperfusion rat model was performed by the technique reported in the literature (10,25). Sprague-Dawley rats (ϳ300 -350 g) were anesthetized with Nembutal administered intraperitoneally (80 -100 mg/kg).…”
Section: In Vivo Myocardial Regional Ischemia-reperfusion Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure for the in vivo ischemia-reperfusion rat model was performed by the technique reported in the literature (10,25). Sprague-Dawley rats (ϳ300 -350 g) were anesthetized with Nembutal administered intraperitoneally (80 -100 mg/kg).…”
Section: In Vivo Myocardial Regional Ischemia-reperfusion Modelmentioning
confidence: 99%
“…Increased NO production and subsequent peroxynitrite (OONO Ϫ ) formation have been detected in the postischemic heart (10,11,14,15). Alterations in the generation of NO occurring in hearts subjected to ischemia/reperfusion have been linked to NO synthase (NOS)-dependent (10,11,14,15) and NOS-independent (18,19) pathways, including involvement of endothelial NOS (eNOS), increased nitrite disproportionation, and increased expression of inducible NO synthase (iNOS) in chronic reperfusion injury (11). Therefore, myocardial ischemia/reperfusion indirectly changes the balance between NO and ROS (especially O 2 . )…”
mentioning
confidence: 99%
“…The regulation of cellular respiration by NO, through the interaction at CcO in the mitochondrial ETC, has been found to be an important factor in many pathophysiological conditions such as ischemia, hyperthermia, etc. (Basu et al 2008;Ilangovan et al 2004a;Zhao et al 2005). A number of studies have been carried out to unravel the mechanistic details of how NO affects the CcO activity at normal and pathologic conditions (Cleeter et al 1994;Cooper and Davies 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is especially important in terms of the regulation of oxygen consumption in various pathological conditions. For example, an ischemia/reperfusion model of the heart has demonstrated that sudden bursts of NO can be measured, and then the heart returns to its normal state (Zhao et al 2005). The oxygen consumption was proven to be lower in that condition, but it is unclear what mechanism causes such a reduction, especially at a low prevailing pO 2 during ischemia (Zhao et al 2005).…”
Section: Hsp90mentioning
confidence: 99%
See 1 more Smart Citation